Implementation and Operational Research: Decentralization Does Not Assure Optimal Delivery of PMTCT and HIV-Exposed Infant Services in a Low Prevalence Setting. (1st December 2015) - Edmonds, Andrew; Feinstein, Lydia; Okitolonda, Vitus; Thompson, Deidre; Kawende, Bienvenu; Behets, Frieda
Abstract : Background: The consequences of decentralizing prevention of mother-to-child HIV transmission and HIV-exposed infant services to antenatal care (ANC)/labor and delivery (L&D) sites from dedicated HIV care and treatment (C&T) centers remain unknown, particularly in low prevalence settings. Methods: In a cohort of mother–infant pairs, we compared delivery of routine services at ANC/L&D and C&T facilities in Kinshasa, Democratic Republic of Congo from 2010–2013, using methods accounting for competing risks (eg, death). Women could opt to receive interventions at 90 decentralized ANC/L&D sites, or 2 affiliated C&T centers. Additionally, we assessed decentralization's population-level impacts by comparing proportions of women and infants receiving interventions before (2009–2010) and after (2011–2013) decentralization. Results: Among newly HIV-diagnosed women (N = 1482), the 14-week cumulative incidence of receiving the package of CD4 testing and zidovudine or antiretroviral therapy was less at ANC/L&D [66%; 95% confidence interval (CI): 63% to 69%] than at C&T (88%; 95% CI: 83% to 92%) sites (subdistribution hazard ratio, 0.62; 95% CI: 0.55 to 0.69). Delivery of cotrimoxazole and DNA polymerase chain reaction testing to HIV-exposed infants (N = 1182) was inferior at ANC/L&D sites (subdistribution hazard ratio, 0.84; 95% CI: 0.76 to 0.92); the 10-month cumulative incidence of the package at ANC/L&D sites was 89% (95% CI: 82% to 93%) versus 97% (95% CI: 93% to 99%) at C&T centers. Receipt of the pregnancy (20% of 1518, to 64% of 1405) and infant (16%–31%) packages improved post decentralization. Conclusions: Services were delivered less efficiently at ANC/L&D sites than C&T centers. Although access improved with decentralization, its potential cannot be realized without sufficient and sustained support. Abstract : Supplemental Digital Content is Available in the Text.